Predictors of Health-related Quality of Life in Irritable Bowel Syndrome Patients Compared With Healthy Individuals. Issue 4 (April 2019) - Addante, Raymond; Naliboff, Bruce; Shih, Wendy; Presson, Angela P.; Tillisch, Kirsten; Mayer, Emeran A.; Chang, Lin
Abstract : Background: Irritable bowel syndrome (IBS) reduces health-related quality of life (HRQOL). It is unclear how having IBS modifies the impact of gastrointestinal (GI), psychosocial, and somatic symptom variables on HRQOL compared with healthy controls (HCs). Aims: (1) Determine psychosocial, somatic, and physical status variables most predictive of HRQOL in IBS and HCs and (2) determine if IBS status modifies relationships between predictive factors and HRQOL. Methods: IBS patients and HCs completed validated questionnaires measuring GI symptoms, psychosocial/somatic variables, and physical [physical component score (PCS)] and mental [mental component score (MCS)] HRQOL via the Short-Form-36. Associations between these variables and HRQOL were evaluated with multiple linear regressions. Variables were standardized to determine the strongest predictors of HRQOL. Statistical significance level was 0.01. Results: Mean HRQOL was higher in 417 HCs versus 290 IBS subjects (PCS: 55.6 vs. 48.6, P <0.001; MCS: 53.7 vs. 44.8, P <0.001). The GI symptom measures were negatively associated with PCS in IBS, but only usual severity was associated with MCS ( P <0.01). In all subjects, psychosocial and somatic measures were associated with MCS and not PCS excluding GI symptom anxiety, which correlated with both ( P <0.01). The strongest predictor of MCS was perceived stress in IBS and depression symptoms in HCs. GI symptom anxiety was the strongest predictor of PCS in both. Greater perceived stress and somatic symptom severity and less mindfulness was linked to larger reductions in HRQOL for IBS compared with HCs ( P <0.01). Conclusions: GI symptom severity and anxiety correlate with PCS, whereas psychosocial/somatic measures parallel MCS. However, HRQOL is comparable in IBS and HCs when perceived stress, somatic symptom severity, and mindfulness are at optimal levels. These findings may have important implications in the management of IBS.